Revealing the multi-target destruction induced by proanthocyanidins against Acetobacter sp. at the molecular level - Ren, Er-Fang; Feng, Xiaoqin; Feng, Yuanxin; Li, Kai; Zeng, Xin-An; Wen, Qing-Hui; Cai, Jin-Lin; Han, Zhong; Chen, Shan; Niu, Debao (Frontiers in Microbiology, 2025)
Proanthocyanidins, which are polyphenolic compounds resulting from the condensation of monomeric flavan-3-ols, exhibit antibacterial activity. This study aimed to investigate the impact of proanthocyanidins on the growth and cell membrane of Acetobacter sp., as well as explore their interaction with intracellular macromolecules to comprehensively elucidate the inhibitory mechanism against Acetobacter sp. The results revealed that proanthocyanidins effectively inhibited the growth of Acetobacter sp., with a minimum inhibitory concentration (MIC) of 2.5 mg/mL. Proanthocyanidins disrupted the cellular morphology and membrane integrity of Acetobacter sp., and affected the structure of cell membranes by interaction with membrane proteins. Meanwhile, exposure to proanthocyanidins led to an elevation in reactive oxygen species (ROS) levels within Acetobacter sp., causing oxidative damage to the cell membrane. Moreover, there was a modification in the composition of fatty acids within the cell membrane, characterized by an increased proportion of unsaturated fatty acids (UFAs), consequently enhancing membrane fluidity. In addition, proanthocyanidins caused a significant decrease in the activities of Alcohol dehydrogenase (ADH) and Aldehyde dehydrogenase (ALDH), and interacted with DNA through groove binding, thereby inhibiting cell function. In conclusion, this study provides evidence that proanthocyanidins can effectively inhibit the growth and reproduction of Acetobacter sp. by destroying cell membranes and affecting intracellular macromolecules.